Isolation ofBdellovibriosp. from soil samples in Mexico and their potential applications in control of pathogens - Oyedara, Omotayo Opemipo; De Luna Santillana, Erick de Jesus; Olguin Rodriguez, Omar; Guo, Xianwu; Mendoza Villa, Marco Antonio; Menchaca Arredondo, Jorge Luis; Elufisan, Temidayo Oluyomi; Garza Hernandez, Javier Alfonso; García León, Israel; Rodríguez Pérez, Mario Alberto (2016)
In this study, two strains of Bdellovibrio were isolated from soil samples using the culture-dependent technique and two members of the family Enterobacteriaceae (Klebsiella sp. and Salmonella sp.) as prey. The Bdellovibrio strains were bacteriolytic, plaque-forming, and highly motile gram-negative bacteria. We identified and confirmed the Bdellovibrio strains using microscopy, PCR amplification, and sequencing of the 16S rRNA gene. They were observed to be different strains based on hit locus and prey range analyses. Here, the first report on Bdellovibrio strains isolated from soil in Mexico corroborates earlier report indicating that populations of Bdellovibrio found in soil are heterogeneous thereby the need to identify the various strains.